Nitrogen levels influence barrenness and sterility of maize varieties under different establishment methods during hot spring in western Terai of Nepal - Marahatta, S. (Journal of Agriculture and Forestry University, 2020)
The national average yield of maize is less than its potential yield in Nepal mainly due to poor agronomic management and adverse climatic conditions. The effect of no-tillage combined with retention of previous crop residues and varying nitrogen fertilizer levels on barrenness, sterility, and yield of open pollinated (OP), and hybrid maize varieties were analyzed in the Western Terai region of Nepal during 2011 and 2012. The treatments included factorial combinations of two establishment methods, (a) conservation agriculture (CA; i.e., no-till with crop residue retention from previous crops) and (b) conventional practice (i.e., conventional tillage without residue retention); two varieties (OP ‘Rampur Composite’ and hybrid ‘Rajkumar); and four N fertilizer levels [(0, 60, 120 and 180 kg ha-1 (during 2011), and 0, 80, 160 and 240 kg ha-1 (during 2012)] arranged in strip plot design to grow maize under rice-mustard-maize cropping system with three replications. Data on sterility, barrenness and yield were analyzed by using R Studio. The effect of barrenness and sterility on the grain yield was negative and significant during both the years. Both barrenness and sterility were higher (by 58.28 and 12.35%, respectively) in 2012 as compared to the 2011, also due to higher temperature and low rainfall. Higher nitrogen uptake under CA resulted the lower barrenness and sterility percentage, and hence the higher grains yield (9%). Barrenness did not effect by varieties (p>0.05), but the sterility (p